Orbital Lyme Disease: MR Imaging before and after Treatment: Case Report - Fatterpekar, Girish M.; Gottesman, Robin I.; Sacher, Michael; Som, Peter M. (American Journal of Neuroradiology, 2002)
Summary: Lyme disease is a multi-system organ disease caused by Borrelia burgdorferi. Although ocular manifestations have been reported, these remain a rare feature of the disease. To our knowledge, the radiology literature has not documented orbital Lyme disease both before and after treatment. We present the MR imaging findings of florid Lyme disease affecting the extraocular muscles in a 46-year-old man. A follow-up MR imaging study performed 6 months after a course of antibiotic therapy revealed complete resolution of the myositic changes.